“Just Pull a Bardot”: Subtitling French Cultural References in “Call My Agent” - Lessinger, Enora (Journal of Audiovisual Translation, 2025)
The translation of cultural references has taken centre stage in translation studies in the last few decades, particularly since the cultural turn observed in translation studies from the 1980s onwards. With the emergence of audiovisual translation (AVT) as an increasingly important subfield of translation studies, new tailored typologies of cultural references and corresponding translation strategies started appearing at the turn of the century. This paper investigates the interplay between the multiple sets of challenges faced by interlingual subtitlers dealing with source texts where cultural references abound, through a case study of the subtitles in English and Spanish of the French series “Call My Agent” (“Dix pour cent”). Relying primarily on Newmark’s classification (1988) of culture-specific items (CSIs) and Pedersen’s typology (2011) of translation strategies for extralinguistic cultural references (ECRs), I provide a contrastive overview of the strategies used for the translation of cultural references in both languages. The results obtained show that foreignisation prevails in both English and Spanish, and that French cultural references with high cultural significance (e.g. cuisine, fashion and cinema) are more likely to be foreignised. Lay summary The French series “Call My Agent” (“Dix pour cent”) is rich in cultural references to French cuisine, fashion, arts, and more. Translating these references into other languages, such as English and Spanish, presents unique challenges. This study explores how cultural elements in the series are adapted for subtitles and identifies trends in subtitling strategies. Using Pedersen's 2011 typology of cultural references, the analysis reveals that the dominant approach in both languages is “foreignisation” – leaving cultural references unchanged or minimally adapted. Interestingly, the study finds that elements tied to prestigious and internationally-renowned aspects of French culture, such as cinema and luxury brands, are more likely to be retained in the English and Spanish subtitles. Conversely, references related to everyday life, like government or transport, are often simplified or adapted to better suit the target audience. This nuanced approach ensures that the series remains accessible while preserving its cultural identity. The findings contribute to understanding how subtitlers balance cultural authenticity and audience comprehension. They also reflect broader shifts in subtitling norms, driven by global streaming platforms like Netflix, which increasingly cater to culturally curious viewers seeking authentic international content.